Cis-regulatory chromatin loops arise before TADs and gene activation, and are independent of cell fate during early Drosophila development - Espinola, Sergio Martin; Götz, Markus; Bellec, Maelle; Messina, Olivier; Fiche, Jean Bernard; Houbron, Christophe; Dejean, Matthieu; Reim, Ingolf; Cardozo Gizzi, Andrés M.; Lagha, Mounia; Nollmann, Marcelo (Nature Genetics, 2021)
Acquisition of cell fate is thought to rely on the specific interaction of remote cis-regulatory modules (CRMs), for example, enhancers and target promoters. However, the precise interplay between chromatin structure and gene expression is still unclear, particularly within multicellular developing organisms. In the present study, we employ Hi-M, a single-cell spatial genomics approach, to detect CRM–promoter looping interactions within topologically associating domains (TADs) during early Drosophila development. By comparing cis-regulatory loops in alternate cell types, we show that physical proximity does not necessarily instruct transcriptional states. Moreover, multi-way analyses reveal that multiple CRMs spatially coalesce to form hubs. Loops and CRM hubs are established early during development, before the emergence of TADs. Moreover, CRM hubs are formed, in part, via the action of the pioneer transcription factor Zelda and precede transcriptional activation. Our approach provides insight into the role of CRM–promoter interactions in defining transcriptional states, as well as distinct cell types.
CRIS-Team Scopus Importer:2021-04-16